Estudo da associação entre ansiedade e susceptibilidade à epilepsia do lobo temporal em ratos - Kohek, Silvia Regina Bica [UNIFESP] (2010)
Subjects with temporal lobe epilepsy (TLE) present an heterogeneous response to pharmacotherapy. This heterogeneity results from physiological differences that might be caused by preexisting factors such as genetic ones. In many patients with TLE, the prognostic for controling the seizures is satisfactory. A significant proportion of individuals however do not have a good prognostic or suffers from a pharmaco-resistant epilepsy. Another important issue about the individuals with epilepsy is that they´re more susceptible to present some comorbities, such as psychiatric syndromes, anxiety and depression. The sum of these factors demonstrates a great heterogeneity between the individuals that suffer from this medical condition. This different baseline predisposition might turn the individuals more susceptible to epilepsy, pharmaco-resistance and even to associated psychiatric diseases. Therefore, using an initial screening in which animals were submitted to the elevated plus-maze, in the present work we subsequently evaluated the susceptibility to the precipitation of seizures with subthreshold and convulsive doses tested in two different experimental models: pilocarpine (Pilo) and pentilenotetrazole (PTZ). In the Pilo model, in that induction of status epilepticus (SE) leads to epilepsy, we weren´t able to identify differences in the susceptibility to SE, mortality rate or frequency of spontaneous recurrent seizures (SRS) in those animals characterized as anxious when compared to the non-anxious animals. In the other hand, we could observe that in the same model, when tested with subthreshold doses, anxious animals presented a greater likelihood to develop SE when compared to the non-anxious ones. Those animals that presented a greater frequency of SRS also showed a greater neuropeptide Y (NPY) expression in a number of brain regions associated to seizures. Those animals that were injected with Pilo, but didn’t present SE (NSE), had neurobehavioral and neuroanatomical alterations when compared to baseline conditions. We thus propose the use of these NSE animals might be an excellent tool for studying the neuroanatomical and functional alterations seen in epileptogenesis. For the PTZ model, we couldn´t identify differences betwen the anxious and non-anxious animals. Thus, this study allowed us to establish an association between anxiety and temporal lobe epilepsy that seems specific to the experimental model.